Assessment of the Level of Physical Performance of the Women Football Players of the Olympic National Team of Uzbekistan - Fazliddin, Karimov (European Journal of Life Safety and Stability (2660-9630), 2024)
The following article studies the level of physical performance of highly qualified women football players. The survey revealed an insufficiently high level. Recommendations are given for increasing the volume of high-intensity anaerobic-glycolytic and aerobic exercise.